How sick is Austria? – A decision support framework for different evaluations of the burden of disease within the Austrian population based on different data sources - Barbara Glock; Florian Endel; Gottfried Endel; Klaudia Sandholzer; Niki Popper; Christoph Rinner; Georg Duftschmid; Peter Filzmoser; Mehmet Can Mert; Jürgen Holl; Michael Wagner-Pinter (International Journal of Population Data Science, 2017)
ABSTRACT